2014
DOI: 10.1155/2014/983728
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Metal Contents in Portland Type V and MTA-Based Cements

Abstract: The aim of this study was to determine, by Atomic Absorption Spectrometry (AAS), the concentration levels of 11 metals in Type V gray and structural white PC, ProRoot MTA, and MTA Bio. Samples, containing one gram of each tested cement, were prepared and transferred to a 100 mL Teflon tube with a mixture of 7.0 mL of nitric acid and 21 mL of hydrochloric acid. After the reaction, the mixture was filtered and then volumed to 50 mL of distilled water. For each metal, specific patterns were determined from univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Several reports have been published regarding the heavy metal content of MTA cements ; however, limited studies have focused on the levels of Al in these dental biomaterials. Aluminium has diverse adverse health effects, including neurotoxicity , genotoxicity , Alzheimer's disease, dementia, hyperactivity, and learning disorders in children .…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have been published regarding the heavy metal content of MTA cements ; however, limited studies have focused on the levels of Al in these dental biomaterials. Aluminium has diverse adverse health effects, including neurotoxicity , genotoxicity , Alzheimer's disease, dementia, hyperactivity, and learning disorders in children .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have attributed the discoloration effect of MTA to the presence of bismuth in its mixture ( 23 , 28 ). Since the amount of bismuth in the PC is much less than MTA ( 29 ), previous researches concluded that the rate of color change due to use of PC should be lower than MTA ( 14 , 30 ). However, in this study, the rate of color change due to the application of PC in all of the time periods was higher than other materials.…”
Section: Discussionmentioning
confidence: 99%
“…The most common form of As is the inorganic type which comes either as trivalent (III) or pentavalent (V) ( 10 ). Various studies have confirmed the presence of As in MTA and MTA-like cements ( 2 - 4 , 7 , 11 - 16 ). The chemical analysis of dental cements concerning As amount showed equivocal results.…”
Section: Introductionmentioning
confidence: 94%
“…It is also advocated for use as a pulp-capping material due to its biocompatibility and sealing ability ( 1 ). MTA is mainly composed of tricalcium silicate, tricalcium aluminate and tetracalcium aluminoferrite which come from its Portland cement component, in addition to bismuth oxide to give the cement its radiopacity ( 2 , 3 ). Portland cement, the main component of MTA ( 4 ), is a hydraulic material.…”
Section: Introductionmentioning
confidence: 99%